Pesan Dakwah Ustadzah Oki Setiana Dewi Dalam Channel Youtube Oki Setiana Dewi Official: (Studi Kasus Video Berjudul: Saatnya Millenial Hijrah, Begini Tipsnya Ustadzah Oki Setiana Dewi) - Amin Sobar; Endang Trisnawati; Khusni Alhan (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The purpose of this research is to describe and explain the preaching message of Ustadzah Oki Setiana Dewi on the Oki Setiana Dewi Official YouTube channel with the title: It's time for millennial migration, here are Ustadzah Oki Setiana Dewi's tips. Qualitative research methods through a case study approach. Data collection techniques with documentation and data analysis with reduction, data presentation and conclusion. The results of the study: da'wah messages include: (1) hijrah means jihad to be better. (2) hijrah challenges: (a) food, namely having to provide healthy and halal food, (b) fun, namely wasting time for nothing, (c) fashion, which is difficult to cover the genitals, (d) social media, namely often sharing bad things on social media. (3) a good way of migrating with umrah which is supported by the support of the scholars, good physical condition, sufficient finances and sufficient knowledge to carry out umrah.